2018
DOI: 10.3389/fmicb.2018.01879
|View full text |Cite
|
Sign up to set email alerts
|

Human T Lymphotropic Virus and Pulmonary Diseases

Abstract: Human T lymphotropic virus type 1 (HTLV-1) is the etiological agent of HTLV-1-associated myelopathy, and adult T cell lymphoma/leukemia (ATL/L). Pulmonary complications such as alveolitis and bronchiectasis were found in individuals who develop TSP/HAM due to chronic inflammation. These individuals showed image anomalies in CT scans and changes in pulmonary function parameters distinctive of pulmonary disease. Furthermore, infected individuals have a greater susceptibility to pulmonary tuberculosis either due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
0
17
0
1
Order By: Relevance
“…A series of studies has shown the relationship between HTLV-1 and pulmonary diseases. Specifically, HAM/TSP patients displayed lymphocytic inflammation [ 180 , 181 , 182 ] and changes in CT scan images [ 183 , 184 , 185 ]. Severe lung damage is predominantly observed in HTLV-1-associated inflammatory diseases such as HAM/TSP and uveitis due to the presence of high CD4 + CD25 + T lymphocytes, release of cytokines (i.e., IL-2, IL-12, and IFN-γ), inflammatory chemokines (i.e., MIP-1α and IP-10), and expression of ICAM-1 in the bronchioalveolar lavage fluid (BALF) [ 127 , 186 ].…”
Section: Evs In Htlv-1-related Diseasesmentioning
confidence: 99%
“…A series of studies has shown the relationship between HTLV-1 and pulmonary diseases. Specifically, HAM/TSP patients displayed lymphocytic inflammation [ 180 , 181 , 182 ] and changes in CT scan images [ 183 , 184 , 185 ]. Severe lung damage is predominantly observed in HTLV-1-associated inflammatory diseases such as HAM/TSP and uveitis due to the presence of high CD4 + CD25 + T lymphocytes, release of cytokines (i.e., IL-2, IL-12, and IFN-γ), inflammatory chemokines (i.e., MIP-1α and IP-10), and expression of ICAM-1 in the bronchioalveolar lavage fluid (BALF) [ 127 , 186 ].…”
Section: Evs In Htlv-1-related Diseasesmentioning
confidence: 99%
“…[ 1 ] HTLV-1 is linked to two life-threatening illnesses, HTLV-1-associated myelopathy (HAM)/tropical spastic paraparesis (TSP) and HTLV-1-associated malignancy (adult T-cell leukemia/lymphoma [ATLL]). [ 2 ] Furthermore, some ATLL patients and HTLV-1 carriers regularly exhibit pulmonary complications characterized by one of the following forms: lymphocytic interstitial pneumonitis (LIP), alveolitis,[ 3 ] HTLV-1-associated bronchioloalveolar disorder (HABA), bronchopneumopathy,[ 4 5 ] diffuse panbronchiolitis-like disease (DPB), and bronchiectasis. [ 3 ] HTLV-1-associated bronchiectasis is particularly common in the Australian population.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Furthermore, some ATLL patients and HTLV-1 carriers regularly exhibit pulmonary complications characterized by one of the following forms: lymphocytic interstitial pneumonitis (LIP), alveolitis,[ 3 ] HTLV-1-associated bronchioloalveolar disorder (HABA), bronchopneumopathy,[ 4 5 ] diffuse panbronchiolitis-like disease (DPB), and bronchiectasis. [ 3 ] HTLV-1-associated bronchiectasis is particularly common in the Australian population. [ 6 ] The DPB is a severe obstructive respiratory disorder recognized by the appearance of injuries in the respiratory bronchiole.…”
Section: Introductionmentioning
confidence: 99%
“…HTLV integrates the transcribed RNA as a DNA provirus into the cell nucleic acid [12][13][14][15][16], and this simple evolutionary procedure leads to the persistence of the virus and its maintenance in nature and has serious implications for the different clinical and epidemiological outcomes of the infection and diseases associated with the virus. The wide array of clinical outcomes shows the target complexity within the human host (including the CNS, blood, lungs, eyes, muscles, bladder and skin), and several medical specialties have to be involved in the care and treatment of infected and diseased persons [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%